Effect of food on the pharmacokinetics of oxycodone and naltrexone from ALO‐02, an extended release formulation of oxycodone with sequestered naltrexone. Issue 5 (22nd January 2015) - Gandelman, Kuan; Lamson, Michael; Salageanu, Joanne; Bramson, Candace; Matschke, Kyle; Malhotra, Bimal
Abstract What is known and Objective ALO‐02 is being developed as an abuse‐deterrent formulation of extended‐release oxycodone hydrochloride with naltrexone hydrochloride sequestered in the core of pellets contained in capsules. The primary objective of this study was to assess the effects of administration of ALO‐02 capsule whole under fed conditions or sprinkling the pellets from ALO‐02 capsule on applesauce under fasting conditions on the pharmacokinetics (PK) of oxycodone, naltrexone and 6‐ß‐naltrexol compared with ALO‐02 capsule administered whole under fasting conditions. The plasma naltrexone and 6‐ß‐naltrexol concentrations were used to assess the sequestration of naltrexone in the ALO‐02 formulation. The secondary objective was to evaluate the safety and tolerability of single 40 mg doses of ALO‐02 in healthy volunteers. Methods This was an IRB‐approved, open‐label, single‐dose, randomized, 3‐period crossover study in 24 healthy adult volunteers, aged 18–55 years. Each subject was assigned to receive single 40 mg doses of ALO‐02 administered whole (intact capsule) under fasting conditions, administered whole under fed conditions (high‐fat breakfast ∼ 950 calories), or sprinkling the contents of the ALO‐02 capsule (pellets) over applesauce and swallowing the dose without chewing under fasting conditions. Each treatment was separated by a 7‐day washout interval. Plasma samples were analyzed just before dosing through 48 hours postdose for oxycodone, and through 120 hours postdose for naltrexone and its major metabolite, 6‐ß‐naltrexol. Pharmacokinetic parameters included maximum plasma concentration [Cmax], area under the plasma concentration‐time profile from time 0 to infinity [AUCinf] and to the last quantifiable concentration [AUClast], time to Cmax [Tmax], and terminal half life [t1/2]. Adverse events, vital signs, and laboratory parameters were monitored for safety assessment. Results The t1/2 and Tmax values for oxycodone were similar for all 3 treatments. There was a lack of effect of food (whole capsule, fed vs. fasted) or of sprinkling on applesauce (pellets vs. whole capsule, fasted) on oxycodone bioavailability. The Test/Reference ratios of adjusted geometric means for oxycodone AUCinf, AUClast, and Cmax were 99.2%, 100%, and 107%, respectively, for the effect of food; and 101%, 101%, and 97.5%, respectively, for the effect of sprinkling on applesauce. The 90% confidence intervals contained entirely within the bioequivalence limits of 80% to 125% for each comparison. Naltrexone remained sequestered during each treatment, based on the sporadic and low measurable plasma concentrations of naltrexone and 6‐ß‐naltrexol. Single doses of ALO‐02 40 mg were well tolerated, and adverse events were mild, with no apparent difference in frequency for all 3 treatments. What is new and Conclusion Results indicate that ALO‐02 can be administered without regard to food. Also, the contents of ALO‐02 can be sprinkled over applesauce and consumed without chewing as an alternative treatment option by subjects with difficulty swallowing. Naltrexone remained sequestered in the ALO‐02 formulation under all 3 treatments.